A Passive Dynamic Walking Model Based on Knee-Bend Behaviour: Stability and Adaptability for Walking down Steep Slopes. (24th October 2013) - An, Kang; Chen, Qijun
This paper presents a passive dynamic walking model based on knee-bend behaviour, which is inspired by the way human beings walk. The length and mass parameters of human beings are used in the walking model. The knee-bend mechanism of the stance leg is designed in the phase between knee-strike and heel-strike. q * which is the angular difference of the stance leg between the two events, knee-strike and knee-bend, is adjusted in order to find a stable walking motion. The results show that the stable periodic walking motion on a slope of r <0.4 can be found by adjusting q *. Furthermore, with a particular q * in the range of 0.12< q *<0.18, the walker can walk down more steps before falling down on an arbitrary slope. The walking motion is more stable and adaptable than the conventional walking motion, especially for steep slopes.